Kepemimpinan Kepala Madrasah dalam Memberdayakan Tenaga Guru di Madrasah Tsanawiyah Nurul Iman - Mia Amelia; Armida Armida; Najmul Hayat (Management of Islamic Education Department, Faculty of Education and Teacher Training, State Islamic University Sulthan Thaha Saifuddin Jambi, 2020)
This research aims to describe the leadership of madrasah heads in empowering teachers in MTs Nurul Iman Ulu Gedong Jambi City. This study uses qualitative methods. Data collection techniques using observations, interviews, and documentation. The results of the study found there are three forms of empowerment of teachers in MTs Nurul Iman Ulu Gedong Jambi City conducted by the principal, first, forming a teacher learning group so that each teacher can exchange experience, knowledge and information about learning. Second, include teachers in workshops, workshops, seminars, conferences, and trainings related to teaching methods/methods, making RPP, Syllabus, and implementing learning strategies. Third, conduct motivational training for teachers to always improve their learning and teaching skills.